2009
DOI: 10.3201/eid1502.080584
|View full text |Cite
|
Sign up to set email alerts
|

Simian T-Lymphotropic Virus Diversity among Nonhuman Primates, Cameroon

Abstract: Cross-species transmission of retroviruses is common in Cameroon. To determine risk for simian T-cell lymphotropic virus (STLV) transmission from nonhuman primates to hunters, we examined 170 hunter-collected dried blood spots (DBS) from 12 species for STLV. PCR with generic tax and group-specifi c long terminal repeat primers showed that 12 (7%) specimens from 4 nonhuman primate species were infected with STLV. Phylogenetic analyses showed broad diversity of STLV, including novel STLV-1 and STLV-3 sequences a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 34 publications
(68 reference statements)
3
66
2
Order By: Relevance
“…Also for STLV-1 we found that the prevalence is much higher in P. b. badius than in P. r. tephrosceles monkeys, with no overlap found in the 95% CI: 50% in P. b. badius (95% CI, 29 to 71%) and 6.4% in P. r. tephrosceles (95% CI, 0 to 15%) (15). It appears that there is a great deal of variation in the estimated prevalence of STLV-1 in wild primates, ranging from 0 to 89%, depending on species and region (9,25,37,50). Interestingly, with the comparisons possible from our study, it is striking to observe such extreme differences also between closely related primate species.…”
Section: Vol 84 2010 Retroviruses In Western Red Colobus Monkeys 7431mentioning
confidence: 93%
“…Also for STLV-1 we found that the prevalence is much higher in P. b. badius than in P. r. tephrosceles monkeys, with no overlap found in the 95% CI: 50% in P. b. badius (95% CI, 29 to 71%) and 6.4% in P. r. tephrosceles (95% CI, 0 to 15%) (15). It appears that there is a great deal of variation in the estimated prevalence of STLV-1 in wild primates, ranging from 0 to 89%, depending on species and region (9,25,37,50). Interestingly, with the comparisons possible from our study, it is striking to observe such extreme differences also between closely related primate species.…”
Section: Vol 84 2010 Retroviruses In Western Red Colobus Monkeys 7431mentioning
confidence: 93%
“…It has been estimated that more than 20% of NHP hunted for food are infected with SIV (Peeters et al, 2002). HTLV, especially human T-lymphotropic virus type 1 (HTLV1) and human T-lymphotropic virus type 2 (HTLV2), are related to distinct lineages of simian T-lymphotropic viruses (STLV) 1 and 2 (Courgnaud et al, 2004;Sintasath et al, 2009;Wolfe et al, 2005a). A large diversity of HTLV-and STLV1-like viruses have been identified in Central African bushmeat hunters, suggesting that exposure to NHP contributed to the emergence of HTLV in humans (Wolfe et al, 2005a).…”
Section: Bushmeat Hunting and Emerging Infectious Diseasesmentioning
confidence: 99%
“…A substantial proportion of wild-living primates in Central Africa are naturally infected with Simian Immunodeficiency Viruses (SIVs) [161,162,163], Simian T-cell Lymphotropic Viruses (STLVs) [164,165,166,167], Simian Foamy Viruses (SFV) [168] and also Hepatitis B Viruses (HBV) [169].…”
Section: Pathogens In Non-human Primatesmentioning
confidence: 99%